Web application implementation of Android programming learning assistance system and its evaluations - Syaifudin, Y W; Funabiki, N; Kuribayashi, M; Mentari, M; Saputra, P Y; Yunhasnawa, Y; Ulfa, F (IOP conference series. Materials Science and Engineering, 2021)
Currently, Android has been installed on more than 70 percent of the smartphone devices in the world, which has significantly increased the need for Android-based application engineers. Many IT departments in universities and professional schools have included the Android-based programming into the main subjects. To improve Android programming educations, we have developed Android Programming Learning Assistance System (APLAS), a platform to accommodate the students learning Android programming independently. APLAS adopts the test-driven development method to realize automatic validations of students’ answers to the programming assignments. Previously, APLAS has been implemented as a desktop offline application. In this paper, we present a Web application implementation to manage the learning activities online. This implementation consists of three main parts, namely, Validator, Web Interface, and Database System. To evaluate the effectiveness, we offered three learning topics, Basic UI, Basic Activity, and Advanced Widgets, into this Web application, and asked 60 students in Indonesia to solve them. The results showed that the Web application has well been accessed and smoothly utilized by them. The reliability of the validator program was confirmed by handling more than 180 submissions.